"A Study on Knowledge, Attitude and Practice of Secondary School Girls in Qazvin on Iron Deficiency Anemia" - D Shojaeizadeh (Tehran University of Medical Sciences, 2001)
A research was carried out to determine the factors affecting knowledge, attitude and practice of secnodary school girls concerning Iron deficiency anemia, in Quazvin city. The study population consists of 218 Students who were randomly selected form ten secondary schools in a selected area. Aquestionnaire was prepared to collect the data and statistical tests of X2 and regression were employed to analyse the data. The results of the study indicated that 57.3 percent of students had poor knowledge, 54.1 percent unfavorable attitude and 44.5 percent weak practice on iron deficiency anemia. The results also showed that the field of education, the level of education, age, fathers' job and mothers, job had significant relation with knowleadge. There is significant relationship between knowledge and attitudes. It was found that knowledge had significant relationship with practice.